Population dynamics of the pasture leafhopper complex (Hemiptera: Cercopidae) in brachiaria and mombasa grass - Sousa, Westefann Dos Santos [UNESP]; Carvalho Silva, Jorge Luis; Campos, Thiago Souza [UNESP]; De Lima Santos, Joao Victor (Inst Federal Sul Minas Gerais-i Fsuldeminas, 2021)
Pasture leafhoppers are considered highly important pests in forage grasses in Brazil due to their widespread occurrence. This insect is one of the most relevant pests in pasture degradation. In order for the control of spittlebugs to be efficient, it is important to know the population behavior of the species of this insect, identify the period of greatest occurrence, as well as the climatic and environmental conditions that favor the development of the pest. Thus, this study aimed to evaluate the population dynamics of spittlebugs, at a quantitative level, in Brachiaria decumbens and Panicum maximum pastures, associating the results with meteorological data from the municipality of Conceicao do Araguaia, Southeast Para. To study the population dynamics of spittlebugs, samples were taken every two weeks, in two types of pastures aged between 5 and 7 years, kept under rotational grazing, with a stocking of 1.5 animal units. The method of monitoring nymphs and adults of leafhoppers was adopted, through walking within the observation area. The level of infestation of spittlebugs in both forage species was evaluated and all results were submitted to analysis of variance by the F test. It was found that the species B. decumbens had a greater number of adults and nymphs when compared to the forage species P. maximum. The population dynamics of spittlebugs occur gradually according to climatic conditions, and the period with not-so-high temperatures (22 degrees C to 34 degrees C) and good rainfall provide an infestation of this insect pest in the pasture.
Keywords: Insect-Prague; Pasture; Brachiaria decumbens; Panicum maximum